Peningkatan Kapasitas Perangkat Nagari dalam Pemanfaatan Teknologi Sistem Informasi Geografis untuk Pemetaan Topografi dan Tata Guna Lahan di Nagari Sitiung, Kecamatan Sitiung, Kabupaten Dharmasraya - Mohamad Hafrison; Ananda Pramuswari; Natzratul Zahira; Nabila Meilia Putri; Gabriel Abdya Pardede; Anugrah Putra Al Fatih (Aksi Nyata : Jurnal Pengabdian Sosial dan Kemanusiaan, 2025)
Sitiung is a nagari in West Sumatra. It is located in Sitiung District, Dharmasraya Regency, West Sumatra Province. This Nagari has an area of about 32.27 km2 and is about 18 km from Punjung Island, the capital of the regency. It is also the administrative center of Sitiung Sub-district. Mapping was conducted in the area to determine the administrative boundaries between jorong and the topography of the nagari. A map is simply defined as a representation of an area in which symbols indicate information about the area. Due to the fact that maps indirectly serve as a communication tool between the creator and the person reading it, the captions relating to the contents of the map are very important. The more detailed and complete the information contained in the map, the better and higher quality it is. In addition, it is easier for readers and users to use it. Data collection in the field can be done in various ways. Administrative and Topographic maps will be produced from the measurements taken.